Microscopic Colitis : a histopathological study of nine cases - Jayalakshmi, P.; Malik, A.K.; Wong, N.W. (1994)
A retrospective histological analysis of colonic biopsies received by the Department of Pathology, University of Malaya during the 4-year-period between 1990 and 1993 revealed nine cases of microscopic colitis (MC). The ages of the patients ranged from 18 to 53 years. Seven patients were females with a female to male ratio of 3.5 :l. The main clinical symptom was chronic diarrhoea of duration varying from 4 months to 5 years. None of the patients had any systemic illness or were on any prior medication. Colonoscopy and barium enema observations in all the subjects were essentially normal. Colonic biopsies showed diffuse plasmacytic infiltration of the lamina propria, intraepithelial lymphocytic infiltration and normal crypt pattern. To the best of our knowledge, this is the first documented report on MC from Malaysia. It is envisaged that better recognition of this condition by histopathologists would reduce the numbers in the often diagnosed category of "nonspecific colitis".